A Comparative Policy Analysis of HPV Vaccination Guidelines: Actors, Context, Content, and Process Across Eight Countries - Grace K. Kyei; Lingling Zhang (Journal of Nursing Scholarship, 2026)
ABSTRACT Aims To compare HPV vaccination policies across eight countries and examine how actors, context, policy content, and implementation processes influence program performance and coverage outcomes. Design Comparative policy analysis using a qualitative cross‐case document analysis. Data Sources Official national HPV vaccination guidelines, technical advisory documents, WHO and UNICEF monitoring reports, and peer‐reviewed literature published between January 2006 and December 2024. Sources were identified through structured searches of PubMed, CINAHL, Scopus, and Web of Science. Methods The Health Policy Triangle framework guided analysis across four domains: Actors, Context, Content, and Process. A standardized data extraction template was applied across eight countries: Australia, Brazil, Japan, Nigeria, Rwanda, Sweden, the United Kingdom, and the United States. Data were synthesized in comparative matrices and analyzed using iterative cross‐case analysis, with coding verified by a second reviewer. Results Five policy archetypes were identified: school‐based universal programs, decentralized federal models, gender‐neutral vaccination strategies, resource‐constrained but high‐performing systems, and the policy recovery model exemplified by Japan. School‐based delivery supported by nursing and school health workforces consistently achieved the highest and most equitable coverage. Rwanda achieved 98% coverage despite a girls‐only, donor‐supported model, indicating that governance quality and community trust may outweigh policy design alone. The global transition to single‐dose HPV vaccination schedules requires country‐specific adaptation that accounts for population‐based eligibility exceptions and evidence gaps, including the absence of clinical trial data on single‐dose protection in males and against non‐cervical HPV‐associated diseases. Conclusion HPV vaccination outcomes are shaped by governance structures, implementation capacity, nursing workforce infrastructure, and public trust. Strengthening school‐based delivery, expanding single‐dose schedules where supported by evidence, and investing in nursing‐led outreach are critical to accelerating progress toward WHO cervical cancer elimination targets. Impact Nurses are central to HPV vaccination delivery worldwide. This analysis provides evidence to support nursing leadership in advocating for school‐based models, workforce investment, and equitable immunization strategies across diverse health system contexts.